Mixed Reality Approach to Serious Games in Developing Musical Intelligence: A Systematic Mapping Study - Fontana, Paulo Gabriel Alves; Classe, Tadeu Moreira de (Anais do Simpósio Brasileiro de Computação Musical, 2025)
This study presents a systematic review investigating the effectiveness of Mixed Reality (MR)-based serious games in fostering musical intelligence, particularly in the domains of rhythm and melody recognition. By applying the SEGRESS methodology, the authors reviewed 466 articles, ultimately selecting 23 primary studies that met stringent inclusion criteria. The review synthesizes findings across several dimensions, including targeted musical skills, user demographics, technological platforms, assessment methods, and measurable outcomes. Results indicate that most MR serious games emphasize receptive and reproductive musical skills, particularly pitch and melody recognition, with rhythm training comparatively underrepresented. Target audiences predominantly consist of beginners and children, and mobile-based Augmented Reality (AR) emerges as a preferred platform for accessibility. Although studies employed diverse evaluation techniques—ranging from pre/post-tests to user feedback—the majority reported positive impacts on musical learning and engagement. However, gaps persist in research involving intermediate and advanced learners, standardized assessments of musical intelligence, and long-term pedagogical outcomes. This review contributes a foundational synthesis of current evidence and outlines future directions for enhancing the integration of immersive technology in music education.